A semiotic analysis of intergeneric borrowings in print advertisements in Jordan. Issue 1 (1st January 2016) - Al-Momani, Kawakib; Migdadi, Fathi; Badarneh, Muhammad A.
Abstract : This paper presents a semiotic analysis of Arabic print advertisements in Jordan. In particular it investigates the phenomenon of intergeneric borrowings. The focus of the study is to provide interpretation of the connoted meanings of these borrowings in light of the sociocultural context that has given rise to them. It also aims to show how these borrowings and the other signs intersemiotically complement each other to achieve their communicative function. To this end, a variety of print advertisements were collected from three major daily newspapers in Jordan, Al-Rai, Ad-Dustour, and Al-Ghad . The analysis draws on Chandler's model of semiotic analysis. The analysis has revealed that the borrowings in the sample data represent specific values derived from the viewers' sociocultural and ideological repertoire. Some of them have the functions of building rapport through creating a celebrative or humorous atmosphere, word play, word replacement, and ambiguity connoted by references to popular culture and mundane situations, while some have the function of creating credibility, commitment, and morality through references to religious discourse and cultural memory.